Ekwiwalencja językowa i kultu-ro wa w angielskim i rosyjskim przekładzie Wojny polsko-ruskiej pod flagą biało-czerwoną Doroty Masłowskiej - Osadnik, Wacław; Strzelecka, Natalia (Przegląd Rusycystyczny, 2009)
ЯЗЫКОВАЯ И КУЛЬТУРНАЯ ЭКВИВАЛЕНЦИЯ В АНГЛИЙСКОМ И РУССКОМ ПЕРЕВОДАХ ВОЙНЫ ПОЛЬСКО-РУССКОЙ ПОД БЕЛО-КРАСНЫМ ФЛАГОМ ДОРОТЫ МАСЛОВСКОЙ Резюме Статья состоит из двух частей. В первой рассматривается проблема эквиваленции в переводе с исторической точки зрения. Авторы анализируют концепции полной, неполной и нулевой эквиваленций, принимая во внимание разные интерпретации: с древней по полисистемную теории. Вторая часть содержит анализ переводов Войны польско-русской под бело-красным флагом Дороты Масловской на английский и русский языки. Авторы представляют культурную концепцию языка и поведения субкультуры „дресеров”, а потом показывают, как переводчикам повезло со спецификой языка романа и с культурной обусловленностью текста романа в переводах. Результат анализа показывает, что существуют примеры отсутствия перевода некоторых структур оригинала, а также способ существования перевода в языке и культуре селевых. LINGUISTIC AND CULTURAL EQUIVALENCE IN ENGLISH AND RUSSIAN TRANSLATIONS OF THE SNOW WHITE AND RUSSIAN RED BY DOROTA MASLOWSKA Summary The paper consists of two parts. The fi rst one is devoted to the problem of equi-valence in translation from the historical perspective. The authors discuss concepts of full, partial and zero equivalence and their understanding from the ancient times to the polysystem theory. The second part contains an analysis of translations of Wojna polsko-ruska pod fl agą biało-czerwoną by Dorota Masłowska into English and Russian. The authors give a short overview of the cultural approach to the language and of the behavioral patterns of the “street-boys”. Following, they attempt to illustrate how both translators coped with the specifi city of the language of the novel, in order to translate it not only linguistically but also culturally. In the conclusion the authors point to the issues concerning the untranslatability of some of the elements of the source text as well as evaluate how the translated text has been accepted in the target language and culture.